Caves, as touristic attractions in Hungary: Adventure, health, culture, ecotourism - Béki , Piroska; Metzger , József; Lasztovicza , Dóra (Applied Studies in Agribusiness and Commerce, 2016)
Hungary offers abundant opportunities for discovering the mysterious world of caves. In Hungary there are around 4100 caves; although only a small number of them are open to the public, they offer a variety of attractions. As they are an important part of tourism, switching them, exploring them and making them accessible for a wider audience generates interest for visitors from different parts of the country. The adrenaline releasing sports offers us new ways of coping with stress, and has had an increasing importance in our lives in the 21st century. Discovering these underground miracles presents a new challenge for travelers. The interest in caves exploded in the 20th century, when ecotourism, longing to get back to nature, and the goal of improving one’s health became leading motivations for travelling. The present research is aimed at surveying, to what extent students of the recreation department are familiar with the opportunities provided by cave tourism and how up-to-date their related knowledge is. The following work introduces opportunities in cave tourism and intends to expose upon gaps in the related marketing strategy. The research questions are the following: Are students familiar with opportunities of cave tourism? What services do the caves they know offer? Are they up-to-date in cave-related news? On what forums do cave tourism appear?